Inter-Observer and Intra-Observer Reliability of Clinical Assessments in Knee Osteoarthritis - Maricar, Nasimah (J Rheumatol, 2016)
BACKGROUND: Clinical examination of the knee is subject to measurement error. The aim of this analysis was to determine inter- and intra-observer reliability of commonly used clinical tests in patients with knee osteoarthritis(OA). METHODS: We studied subjects with symptomatic knee OA who were participants in an open-label clinical trial of intra-articular steroid therapy. Following standardisation of the clinical test procedures, two clinicians assessed 25 subjects independently at the same visit, and the same clinician assessed 88 subjects over an interval period of 2–10 weeks; in both cases prior to the steroid intervention. Clinical examination included assessment of bony enlargement, crepitus, quadriceps wasting, knee effusion, joint-line and anserine tenderness and knee range of movement(ROM). Intra-class correlation coefficients(ICC), estimated kappa(κ), weighted kappa(κ(ω)) and Bland and Altman plots were used to determine inter- and intra-observer levels of agreement. RESULTS: Using Landis and Koch criteria, inter-observer kappa scores were moderate for patellofemoral joint(κ=0.53) and anserine tenderness(κ=0.48); good for bony enlargement(κ=0.66), quadriceps wasting(κ=0.78), crepitus(κ=0.78), medial tibiofemoral joint tenderness(κ=0.76), and effusion assessed by ballottement(κ=0.73) and bulge sign(κ(ω) =0.78); and excellent for lateral tibiofemoral joint tenderness(κ=1.00), flexion(ICC=0.97) and extension(ICC=0.87) ROM. Intra-observer kappa scores were moderate for lateral tibiofemoral joint tenderness(κ=0.60), good for crepitus(κ=0.78), effusion assessed by ballottement test(κ=0.77), patellofemoral joint(κ=0.66), medial tibiofemoral joint(κ=0.64) and anserine(κ=0.73) tenderness and excellent for effusion assessed by bulge sign(κ(ω) =0.83), bony enlargement(κ=0.98), quadriceps wasting(κ=0.83), flexion(ICC=0.99) and extension(ICC=0.96) ROM. CONCLUSION: Among individuals with symptomatic knee OA, the reliability of clinical examination of the knee was at least good for the majority of clinical signs of knee OA.